2021
DOI: 10.1038/s41598-021-87199-7
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin-1/CCL11 is involved in cell migration in rheumatoid arthritis

Abstract: Eotaxin-1 (CCL11) induces the migration of different leukocyte types by interacting with CCR3. In rheumatoid arthritis (RA), fibroblast-like synoviocytes (FLS) are pathogenic effectors and a major CCR3-expressing cell. The aim of this study was to investigate the expression and function of CCL11 in RA FLS. The expression of CCL11 and CCR3 was evaluated by ELISA, immunofluorescence and quantitative PCR analysis. The CCL11 levels in serum and synovial fluids (SFs) from RA patients were significantly higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…CCL11 and CCR3 production was proven in synovial tissue and synoviocytes of RA-affected joints, with the expression being stimulated by TNF and CCL11 itself. It was also confirmed that chemokine promotes synoviocytes migration during RA [ 18 ]. CCL11/CCR3 axis is also believed to affect bone destruction [ 19 ].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…CCL11 and CCR3 production was proven in synovial tissue and synoviocytes of RA-affected joints, with the expression being stimulated by TNF and CCL11 itself. It was also confirmed that chemokine promotes synoviocytes migration during RA [ 18 ]. CCL11/CCR3 axis is also believed to affect bone destruction [ 19 ].…”
Section: Discussionmentioning
confidence: 86%
“…C–C motif ligand 11 chemokine (CCL11), also described as eotaxin, is a ligand for C–C chemokine receptor 3 (CCR3) with the capacity to bind to other receptors as well [ 18 ]. CCL11 is secreted by: endothelial and epithelial cells, eosinophils, fibroblasts, keratinocytes, smooth muscle cells or chondrocytes [ 19 ], and its expression is induced by TNF and IL-4 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eotaxin is a CC chemokine ligand (CCL) with diverse immunoreactivity, and composes of eotaxin-1 (CCL11), eotaxin-2 (CCL24), and eotaxin-3 (CCL26) (37)(38)(39)(40). Previous studies reported that eotaxin was a pivotal mediator for promoting migration, activation and maturity of eosinophils, and high levels of eotaxin facilitated local and systemic eosinophils recruitment which were involved in the pathophysiology of various autoimmune and inflammatory diseases (41)(42)(43). A recent publication demonstrated that plasma eotaxin concentrations were elevated in chronic rhinosinusitis patients and eotaxin-3 levels positively associated with the degree of mucosal eosinophil infiltration, which FGF, fibroblast growth factor; NGF, nerve growth factor; CTACK, cutaneous T cell attracting chemokine; G-CSF, granulocyte colony stimulating factor; GM-CSF, granulocyte-macrophage colony stimulating factor; GRO, growth-regulated oncogene; HGF, hepatocyte growth factor; IFN, interferon; IL, interleukin; IP, interferon-inducible protein; LIF, leukemia inhibitory factor; MCP, monocyte chemotactic protein; M-CSF, macrophage colony stimulating factor; MIF, macrophage migration inhibitory factor; MIG, monokine induced by interferon-gamma; MIP, macrophage inflammatory protein; PDGF, platelet-derived growth factor; RANTES, regulated on activation in normal T-cell expressed and secreted; SCF, stem cell factor; SCGF, stem cell growth factor; SDF, stromal cell-derived factor; TNF, tumor necrosis factor; TRAIL, tumor necrosis factor related apoptosis inducing ligand; VEGF, vascular endothelial cell growth factor.…”
Section: Discussionmentioning
confidence: 99%